Pengukuran Kinerja Lingkungan dengan Sustainability Balanced Scorecard: Seimbang, Komprehensif, dan Strategis - Burhany, Dian Imanina; Novianty, Ira; Suwondo, Sulistia (Program Studi Akuntansi FPEB UPI, 2021)
More companies care about environment, so environmental performance measurement needs to be done to determine effectiveness of environmental management strategies. Most environmental performance measurement done partially, focused on environmental aspect, and not related to other aspects. Sustainability balanced scorecard (SBSC) modified from the balanced scorecard (BSC) integrates environmental indicators into four BSC perspectives in order to obtain balanced, comprehensive and strategic environmental performance information. This study aims to measure environmental performance using four SBSC perspectives, namely learning and growth, internal business processes, customers, and finance. This study is a case study in a heavy equipment manufacturer. Primary data were analyzed descriptive quantitatively. Study result find that company's environmental performance for learning and growth perspectives, and internal business process perspectives, and Â financial perspective are excellent, while for customer perspective is good. This information become basis for management to determine perspectives and indicators where improvement should be done to improve environmental performance.